EP1174 Female genital tract melanoma: a 12-year case series with expert pathological review. (1st November 2019) - Lewin, J; Ellery, P; Wilkinson, N; Kotsopoulos, I; Olaitan, A
Abstract : Introduction/Background: Malignant melanomas of the female genital tract (FGT) are rare and carry poor prognosis.They have a poorly characterised natural history & lack consensus on optimal management. We reviewed the 12 year experience of a tertiary centre treating this disease. Methodology: A text search of the pathology reporting system was used to identify all FGT malignant melanoma cases from 2007 to present. Electronic patient records were used to record clinical information. Histopathology was reviewed by a gynaecological and dermatological pathology specialist. Data were analysed using Chi square, Mann-Whitney-U, or Student's t-test. Results: We identified 30 cases of FGT melanoma; Mean age at presentation was 64 years (range:32–87). Median Breslow thickness was 4.55 mm. 17 patients were treated by wide local excision, 12 by radical surgery and 3 received no surgical treatment. Median follow-up time was 67 months. Survival rates at 1, 3 and 5 years were 87%, 70% and 67% respectively. 19 presented with lower (vulvar) and 11 presented with upper FGT (vaginal or cervical melanoma). Upper FGT lesions were significantly associated with higher mortality compared to vulval lesions (p=0.002).5 patients were diagnosed at in-situ stage, all of these were lower FGT. Even after removing these from analysis, upper genital tract melanomas were still significantly associated with mortality (p=0.01). There was no association between Breslow thickness and site (p=0.156), or mortality (p=0.857). No association was found between mortality and microscopic ulceration, lymphovascular invasion, pigmentation, or completeness of primary excision. Conclusion: This case series, one of the largest available, helps to further demonstrate the natural history of this rare disease. Patients presented at advanced stage, indicated by high Breslow thickness. Upper FGT melanomas had significantly poorer prognosis than lower FGT melanomas, which was not fully explained by a difference in stage. Disclosure: Nothing to disclose